Automatic Classification and Severity Estimation of Ataxia From Finger Tapping Videos - Nunes, Adonay S.; Kozhemiako, Nataliia; Stephen, Christopher D.; Schmahmann, Jeremy D.; Khan, Sheraz; Gupta, Anoopum S. (Frontiers in Neurology, 2022)
Digital assessments enable objective measurements of ataxia severity and provide informative features that expand upon the information obtained during a clinical examination. In this study, we demonstrate the feasibility of using finger tapping videos to distinguish participants with Ataxia (N = 169) from participants with parkinsonism (N = 78) and from controls (N = 58), and predict their upper extremity and overall disease severity. Features were extracted from the time series representing the distance between the index and thumb and its derivatives. Classification models in ataxia archived areas under the receiver-operating curve of around 0.91, and regression models estimating disease severity obtained correlation coefficients around r = 0.64. Classification and prediction model coefficients were examined and they not only were in accordance, but were in line with clinical observations of ataxia phenotypes where rate and rhythm are altered during upper extremity motor movement.